2017
DOI: 10.1021/acs.jpcb.7b03786
|View full text |Cite
|
Sign up to set email alerts
|

Cosolutes, Crowding, and Protein Folding Kinetics

Abstract: Long accepted as the most important interaction, recent work shows that steric repulsions alone cannot explain the effects of macromolecular cosolutes on the equilibrium thermodynamics of protein stability. Instead, chemical interactions have been shown to modulate, and even dominate, crowding-induced steric repulsions. Here, we use19F NMR to examine the effects of small and large cosolutes on the kinetics of protein folding and unfolding using the metastable 7 kDa N-terminal SH3 domain of the Drosophila signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 110 publications
(351 reference statements)
5
57
0
Order By: Relevance
“…To quantify the enthalpic and entropic components, we assessed ΔHu0' and −TΔSu0' at 308 K and 298 K (Table ). Urea is enthalpically destabilizing but entropically stabilizing whereas TMAO is enthalpically stabilizing but entropically destabilizing as has been observed in other studies …”
Section: Figuresupporting
confidence: 80%
See 1 more Smart Citation
“…To quantify the enthalpic and entropic components, we assessed ΔHu0' and −TΔSu0' at 308 K and 298 K (Table ). Urea is enthalpically destabilizing but entropically stabilizing whereas TMAO is enthalpically stabilizing but entropically destabilizing as has been observed in other studies …”
Section: Figuresupporting
confidence: 80%
“…Urea is enthalpically destabilizing but entropically stabilizing whereas TMAO is enthalpically stabilizing but entropically destabilizing as has been observed in other studies. [42][43][44][45] For Ficoll and dextran, the DH 0 0 u values in solutions of their monomers are smaller than those in polymers, showing that KH1 is enthalpically destabilized in monomers compared to polymers. It appears that the monomers have stronger attractive interactions with the unfolded ensembles than do the polymers, consistent with conclusions from Record's group.…”
Section: Crowding and Confinement Can Oppositely Affect Protein Stabimentioning
confidence: 99%
“…ΔGUF# is expected to be reduced by the excluded volume effect, if the transition state is more compact than the reactant state, as in the case of a protein folding reaction. A very recent study of the Pielak group could dissect the impact of crowding on the activation free energy into enthalpic and entropic contributions and reported on different thermodynamic mechanisms for Ficoll and lysozyme as crowding agents . However, if large‐scale motions between protein domains and thus the intrachain diffusion play a significant role, crowding may reduce the value of k UF,0 .…”
Section: Thermodynamic Concepts Describing the Effects Of Macromolecmentioning
confidence: 99%
“…Av ery recent study of the Pielak group could dissect the impact of crowding on the activation free energy into enthalpic and entropic contributions and reported on different thermodynamic mechanisms for Ficoll and lysozyme as crowding agents. [241] However, if large-scale motions between protein domains and thus the intrachain diffusion play as ignificantr ole, crowdingm ay reduce the value of k UF,0 .T hereby,b oth the internal dynamics and the solventm icroviscosity can contribute to the effective diffusion constant along the folding path. [242] Them icroscopic spatialh eterogeneity of ac rowdeds olution can cause solvent microviscosities that might be much smaller than the bulk viscosity.…”
Section: Kinetics and Increased Viscositymentioning
confidence: 99%
“…A cellular model should also include non-equilibrium processes, for their importance in regulating protein stability (Samiotakis et al 2009;Gershenson and Gierasch 2011;Wang et al 2015;Bui and Hoang 2016;Gorensek-Benitez et al 2017). Toward this goal, recent simulations of cotranslational folding showed that translation rates may affect the structure and stability of misfolding-prone proteins (Trovato and O'Brien 2017), as well as of multidomain proteins (Tanaka et al 2015).…”
Section: Toward Realistic Molecular Simulations Of Cellular Eventsmentioning
confidence: 99%